Reading rhetorical texts : an introduction to criticism - Andrews, James Robertson, 1936- (Houghton Mifflin, 1997)
This book is divided into four parts: Critical Foundations; Critical Readings and Commentary; Alternative Readings; and Critical Reading: Sample Studies.